Observational Multicenter Study of a Direct-to-CT Protocol for EMS-transported Patients with Suspected Stroke. (2nd January 2018) - Cone, David C.; Cooley, Craig; Ferguson, Jeffrey; Harrell, Andrew J.; Luk, Jeffrey H.; Martin-Gill, Christian; Marquis, Sean W.; Pasichow, Scott
Abstract: Objective: In an effort to decrease door-to-needle times for patients with acute ischemic stroke, some hospitals have begun taking stable EMS patients with suspected stroke directly from the ambulance to the CT scanner, then to an emergency department (ED) bed for evaluation. Minimal data exist regarding the potential for time savings with such a protocol. The study hypothesis was that a direct-to-CT protocol would be associated with decreases in both door-to-CT-ordered and door-to-needle times.Methods: An observational, multicenter before/after study was conducted of time/process measures at hospitals that have implemented direct-to-CT protocols for patients transported by EMS with suspected stroke. Participating hospitals submitted data on at least the last 50 "EMS stroke alert" patients before the launch of the direct-to-CT protocol, and at least the first 50 patients after. Time elements studied were arrival at the ED, time the head CT was ordered, and time tPA was started. Data were submitted in blinded fashion (patient and hospital identifiers removed); at the time of data analysis, the lead investigator was unaware of which data came from which hospital. Simple descriptive statistics were used, along with the Mann-Whitney test to compare time medians.Results: Seven hospitals contributed data on 1040 patients (529 "before" and 511 "after"); 512 were male, and 627 had final diagnoses of ischemic stroke, of whom 275 received tPA. The median door-to-CT-ordered time for all patients was 7 minutes in the before phase, and 4 minutes after (difference 3 minutes, p = < 0.0001); similarly, the median door-to-CT-started time was 6 minutes "before" and 10 minutes after ( p < 0.0001). The median door-to-needle time for all patients given tPA was 42 minutes before, and 44 minutes after ( p = 0.78). Four hospitals had modest decreases in door-to-CT-ordered time (of 2, 4, 2, and 5 minutes), and only one hospital had a decrease in door-to-needle time (32 min vs 26 min, p = 0.012).Conclusions: In this sample from seven hospitals, a minimal reduction in door-to-CT-ordered and door-to-CT-started time, but no change in door-to-needle time, was found for EMS patients with suspected stroke taken directly to the CT scanner, compared to those evaluated in the ED prior to CT.